Preparation of Reflective Thermal Insulation Coating with Molybdenum Tailings as Filler - Jiantao LI; Bingzheng HAN; Chengfang QIAO; Jiale LI; Wang WANG (Kuangchan zonghe liyong)
This is an article in the field of mineral materials. The accumulation of molybdenum tailings has caused many environmental problems, and there is an urgent need for comprehensive utilization. The study aims to use molybdenum tailings as fillers, supplemented by base materials, functional fillers, and additives to prepare reflective insulation coatings for building exterior walls, with the aim of achieving high-value utilization of molybdenum tailings and depleting molybdenum tailings waste. The optimal formula for exterior wall reflective insulation coating was determined through single factor and orthogonal experimental optimization, and the coating performance was tested and analyzed. The results showed that the reflectivity of the coating was 91.6%, the thermal conductivity of the coating was 0.062 W/(m∙K), and other properties met the requirements of GB/T 25261—2018.